How to speak Brit : the quintessential guide to the King's English, Cockney slang, and other flummoxing British phrases - Moore, C. J. (Christopher J.) (How to speak Brit, 2014)
" The quintessential A to Z guide to British English-perfect for every egghead and bluestocking looking to conquer the language barrier. Oscar Wilde once said the Brits have "everything in common with America nowadays except, of course, language." Any visitor to Old Blighty can sympathize with Mr. Wilde. After all, even fluent English speakers can be at sixes and sevens when told to pick up the "dog and bone" or "head to the loo," so they can "spend a penny." Wherever did these peculiar expressions come from? British author Christopher J. Moore made a name for himself on this side of the pond with the sleeper success of his previous book, In Other Words. Now, Moore draws on history, literature, pop culture, and his own heritage to explore the phrases that most embody the British character. He traces the linguistic influence of writers from Chaucer to Shakespeare and Dickens to Wodehouse, and unravels the complexity Brits manage to imbue in seemingly innocuous phrases like "All right." Along the way, Moore reveals the uniquely British origins of some of the English language's more curious sayings. For example: Who is Bob and how did he become your uncle? Why do we refer to powerless politicians as "lame ducks"? How did "posh" become such a stylish word?Part language guide, part cultural study, How to Speak Brit is the perfect addition to every Anglophile's library and an entertaining primer that will charm the linguistic-minded legions. "--